Parallel Metaheuristics 2005
DOI: 10.1002/0471739383.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Variable Neighborhood Search

Abstract: Les textes publiés dans la série des rapports de recherche HEC n'engagent que la responsabilité de leurs auteurs. La publication de ces rapports de recherche bénéficie d'une subvention du Fonds québécois de la recherche sur la nature et les technologies. AbstractVariable Neighborhood Search (VNS) is a recent and effective metaheuristic for solving combinatorial and global optimization problems. It is capable of escaping from the local optima by systematic changes of the neighborhood structures within the sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The final step is used to verify if the stopping criterion is met. Recent developments and applications of VNS may be found in [17,27].…”
Section: Meta-heuristics With Parallel Lsmentioning
confidence: 99%
“…The final step is used to verify if the stopping criterion is met. Recent developments and applications of VNS may be found in [17,27].…”
Section: Meta-heuristics With Parallel Lsmentioning
confidence: 99%
“…Most of the reviews that we found focus on parallel optimization regarding particular methodologies. While branch-and-bound algorithms have been reviewed by Gendron and Crainic [1994], the majority of methodological literature reviews have focused on metaheuristics: reviews have addressed tabu search (TS) [Crainic et al, 2005], simulated annealing (SA) [Aydin and Yigit, 2005], variable neighborhood search (VNS) [Pérez et al, 2005], Greedy Randomized Adaptive Search Procedures (GRASPs) [Resende and Ribeiro, 2005], swarm intelligence algorithms [Tan and Ding, 2016], particle swarm optimization algorithms [Zhang et al, 2015], and different types of evolutionary algorithms, including genetic algorithms (GAs) [Adamidis, ]. Application-and discipline-oriented reviews of parallel optimization have been provided for routing problems in logistics and for parallel metaheuristics in the fields of telecommunications and bioinformatics [Nesmachnow et al, 2005, Trelles and Rodriguez, 2005, Martins and Ribeiro, 2006].…”
mentioning
confidence: 99%